Estructura genética y poblacional de Bovinos Brown Swiss del INIA en Puno - Mamani Cato, Rubén Herberht; Gallegos Acero, Roberto F.; Checalla Mamani, Vilk Modesto; Condori Rojas, Nicoll (Instituto Nacional de Innovación Agraria, 2021)
13 páginas